Unleashing the potential of Indonesian EFL high school students' writing proficiency and self-regulated learning through written corrective feedback - Afreilyanti, Elizabet; Kuswandono, Paulus (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Despite the existence of many studies on EFL student writing proficiency, little work reports how written corrective feedback influences EFL senior high school students